Psychoeducational Intervention: An Effort to Prevent Early Marriage at Sebatik - Cici Ismuniar; Emmy Ardiwinata; Nuraisyah Bashir (Bisma The Journal of Counseling, 2025)
Child marriage constitutes a violation of child rights and a form of gender-based violence that significantly impacts human capital and restricts children's life opportunities. This phenomenon is highly alarming, where its prevalence is among the highest nationally, thus necessitating a focused intervention. The primary goal of this research is to develop a structured psychoeducation intervention design and evaluate its effectiveness by analyzing students' knowledge improvement concerning the definition, causes, impacts, and prevention efforts of child marriage. The study employed a quantitative experimental method with a One-group Pretest-Posttest design on students using purposive sampling. Data were collected via questionnaires and analyzed using the t-test. Results indicate a highly significant increase in post-test scores (M=116.92) compared to pre-test scores (M=101.08), with a mean difference of 15.83 (p < 0.05). The greatest improvement was observed in the variables related to causes and prevention efforts, demonstrating that psychoeducation is effective in enhancing both students' theoretical and practical awareness. The psychoeducation intervention successfully empowered students, establishing it as a crucial and sustainable strategy in the efforts to protect child rights in border regions.